The Effectiveness of Electronic Health Uptake in Diabetes Mellitus Patients: A Meta-Analysis - Eni Nur Rahmawati; Didik Gunawan Tamtomo; Bhisma Murti (Journal of Health Promotion and Behavior, 2021)
Background: Diabetes is a chronic disease in the form of a metabolic disorder characterized by blood sugar levels that exceed normal limits. The cause of the increase in blood sugar levels is the basis for grouping the type of Diabetes. This study aims to examine the effectiveness of the use of electronic health in patients with diabetes mellitus.Subjects and Method: Meta-analysis was carried out using PICO as follows: The population in this study were patients with diabetes mellitus. Intervention in the form of the use of electronic health. Comparison in the form of direct consultation. The outcome is a decrease in HbA1c levels. Meta-analytical studies were applied to this study with electronic data sources: Google Scholar, MEDLINE/PubMed, Science Direct and ProQuest. The article used is a full-text article with a Randomized Control Trial (RCT) study design. There are 9 articles used in this study with a total sample of 1.137 people who were divided into two groups (568 people in the electronic health group and 569 people in the direct consultation group). Articles were analyzed using the Review Manager 5.3 application. The results of this study aim to determine the Standardized Mean difference (SMD) and the heterogeneity of the research sample.Results: There was a high heterogeneity between one experiment and another (I2=91%; P<0.001) so the Random Effect Model (REM) was used. The use of Electronic Health help reduces HbA1c levels with Standardized Mean Different (SMD) by 0.39 compared to direct consultation (SMD= -0.39; 95% CI = -0.79 to -0.01; p=0.050).Conclusion: The use of electronic health help reduces HbA1c levels in diabetes mellitus patients with Standardized Mean Different (SMD) by 0.39 compared to direct consultation.Keywords: Electronic Health, Diabetes Mellitus, HbA1cCorrespondence:Eni Nur Rahmawati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: eninur_rahma@udb.ac.id. Mobile: +6285743748528.Journal of Health Promotion and Behavior (2021), 06(03): 176-187DOI: https://doi.org/10.26911/thejhpb.2021.06.03.02